An analysis of some presuppositions underlying the concepts of meritocracy and ability as presented in Greaney and Kellaghan study - Lynch, Kathleen (Economic & Social Studies, 1985)
Two key concepts in Greaney and Kellaghan's book are those of meritocracy and ability. This paper sets out to present a critical evaluation of the major sociological and educational presuppositions on which these are based. By elaborating on the conceptual complexities of these two ideas we try to show how the scientific categories within which we formulate research issues are themselves value-laden. The authors' mode of analysis in this study was highly quantitative but largely atheoretical, conceptual issues, therefore, were not treated analytically or critically. Their failure to treat key concepts problematically belies the intense academic debate as to the nature of these phenomena. More importantly perhaps it leads to an oversimplification of the problems of social and educational equality, it does so by concealing the class-specific interests which the very notion of meritocracy, and their particular interpretation of the concept of ability, are likely to serve.
Keywords: Social mobility; Educational equality